Design and Development of a Vertical-Type Hydraulic Ram Pump Simulator - Widiawaty, Candra Damis; Millah, Azzam; Rasyid, Muhammad; Putri, Nuke Earlyana; Putri, Maytasha Gusti; Nurdiansyah, Muhammad; Fatin, Shafa Amatullah (Politeknik Negeri Jakarta, 2026)
The hydraulic ram pump is one form of green energy used to convey water by utilizing the water hammer effect. The main parameter influencing the performance of a hydraulic ram pump is the water energy source. Most researchers modify the hydraulic ram pump design based on the installation site, which limits the variation of design or operating conditions due to the complexity and geographical constraints in the field. The main contribution of this work is the development of a vertical-type hydraulic ram pump simulator that enables controlled laboratory investigation of design modifications and operating parameter optimization, overcoming the limitations of site-specific field installations. The research applies a design and experimental method. The design process begins with defining design constraints and calculating the flow based on the Bernoulli equation, flow rate, head loss, and rule-of-thumb operational conditions for hydraulic ram pumps. The results show that the flow rate significantly affects the pump efficiency. Flow rates of 0.6 L/s, 0.8 L/s, 0.9 L/s, and 1 L/s. The range pressure of P1 are 50-60 mBar, 8-90 mBar, 80-120 mBar, and 100-140 mBar. The range pressure of P2 are 120-125 mBar, 20-40mBar, 20-40mBar, and 85-120 mBar. Therefore, the yielded average efficiencies are 5.3%, 1.6%, 3.9%, and 3.5%, respectively. The developed hydraulic ram pump simulator achieved the highest efficiency (5.3%) at a flow rate of 0.6 L/s, P1 50-60 mBar, and P2 120-125 mBar. It can be observed that an increase in drive pipe flow rate does not always correspond to an increase in efficiency. However, the efficiency is more strongly determined by the pressure generated by the water hammer.